Analisis Debit Sungai dengan Menggunakan Model SWATpada DAS Cipasauran, Banten - Maulana Ibrahim Rau; Nora Pandjaitan; Asep Sapei (Jurnal Keteknikan Pertanian, 2015)
Total water demand at non industrial and industrial region in Cilegon is increasing. With its water production capacity of 2,000 l/s, PT Krakatau Tirta Industri (KTI) cannot fulfill the amount number of demand from the industrial and domestic sectors at Cilegon. To cover the shortage of water supply of ±600 l/s, PT KTI requires taking water from Cipasauran Watershed. The objective of this study was to analyze river discharge of Cipasauran Watershed using SWAT model. Input data such as soil characteristics, climate data, landuse, and hydrology data at the area of the watershed were gathered and put at the data input file. In SWAT simulation, 4 processes were done, i.e. watershed delineation, hydrological response unit (HRU) forming, data process and SWAT simulation, and visualization process. The result showed that the daily and monthly calibration process crossed 84% and 83% with the 95PPU area, with daily and monthly p-factor value of 0.84 and 0.83. Thus, calibrated model result was valid, though R2 and NS value were not satisfied. Using the validated SWAT model, the daily discharge in Cipasauran Watershed was about 0 - 3.309 m3/s, whereas the monthly discharge was 0.648 - 3.266 m3/s. This showed that daily and monthly PT KTI’s water demand of 0.6 m3/s were fulfilled about 98.22% and 100%. Within the future time, the SWAT model could be potentially used as an assessment for predictive scenarios. However, to gain optimum results, well-observed and precise data is highly required, especially for such calibrations and validations.